English File. Intermediate teacher's guide - Latham-Koenig C. Christina; Oxender C. Clive; Lambert J. Jerry; Lowy A. Anna; Mabbott K. Krysia (Oxford, Oxford University Press, 2019)
The English File fourth edition Teacher's Guide with Teacher's Resource Centre gives you everything you need to create flexible lessons that work for your students. The Teacher's Guide offers a comprehensive walk-through guide to every lesson, in every unit of the Student's Book, along with at least two photocopiable activities for each lesson. The Teacher's Resource Centre allows you to manage video, audio, answer keys, tests and much more all in one place online.